The Great Mutiny - Dugan, James (London Mayflower Books, 1965)
A gripping and thorough account of the great British naval mutinies at Spithead and the Nore in 1797 when the sailors of the Royal Navy rose up in revolt against their appalling working conditions and withholding of pay. The author contrasts the unexpected success of the Spithead mutiny, in which the sailors were granted most of their demands, with the story of the Nore mutiny where, under the leadership of a seaman called Richard Parker, the revolt took an altogether more tragic course.
Include Appendices, Bibliography and Index.
Surveys the corrupt conditions of Georgian England in 1797 and chronicles the British fleet's "sit down strike" at Portsmouth and Spithead - the largest naval insurrection in history.
Keywords: Nore Mutiny (1797) -- Spithead Mutiny (1797) -- George III, King of Great Britain, 1738-1820